Application of Three-Dimensional Printed Customized Surgical Plates for Mandibular Reconstruction: Report of Consecutive Cases and Long-Term Postoperative Evaluation. Issue 7 (30th October 2021) - Ma, Hongyang; Van Dessel, Jeroen; Bila, Michel; Sun, Yi; Politis, Constantinus; Jacobs, Reinhilde
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: This study aims to evaluate the use of customized surgical plates in patients with mandibular defects concerning postoperative aesthetics and functional outcomes during the 2-year follow-up. Preoperative virtual surgical plans and patient-specific three-dimensional printed plates were tailored for consecutive patients. Preoperative preparation, surgical produces, postoperative aesthetics, and functional outcomes were described in detail. The average follow-up period was over 2 years. In the presented clinical cases, aesthetic and functional outcomes were reported to be satisfactory.